Potential of phytochemicals as a treatment for Alzheimer’s disease: evaluation of anticholinesterase activity, antioxidant properties, and cytotoxicity - Aljadaan, Adel (2025)
Alzheimer's disease (AD) significantly impacts individuals, families, and global healthcare systems, characterised by cognitive decline, memory impairment, and oxidative stress. This study investigated the potential of phytochemicals as therapeutic agents for Alzheimer's disease (AD) through an integrated approach that combines in silico and in vitro methodologies. Docking studies indicated that rutin exhibited the strongest binding affinity for acetylcholinesterase (AChE) at -14.81 kcal/mol, whereas silibinin demonstrated the highest affinity for butyrylcholinesterase (BuChE) at -9.55 kcal/mol. In vitro, assays identified berberine as the most potent AChE inhibitor, with an IC50 value of 60.99 µM, and silibinin as the most effective BuChE inhibitor, with an IC50 value of 48.95 µM. Antioxidant assessments revealed that chlorogenic acid displayed the most significant DPPH scavenging activity, with an EC50 of 126.1 µM, while silymarin was most effective in inhibiting lipid peroxidation, yielding an EC50 of 35.6 µM. Cytotoxicity evaluations indicated that berberine and quercetin-3-β-glucoside exhibited minimal toxic effects, consistent with in silico predictions, whereas rutin resulted in elevated reactive oxygen species (ROS) generation. Ex vivo analyses demonstrated a significant reduction in superoxide dismutase 1 (SOD1) levels and increased protein carbonylation in AD samples, suggesting their potential role as markers of oxidative stress. These findings highlight the potential of phytochemicals as multifunctional therapeutic agents for Alzheimer's disease (AD), demonstrating promising efficacy and low toxicity.